2020
DOI: 10.3174/ajnr.a6595
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic Posterior Reversible Encephalopathy Syndrome as a Manifestation of COVID-19 Infection

Abstract: We describe 2 hospitalized patients with confirmed coronavirus 19 (COVID-19) infection in whom brain imaging showed hemorrhagic posterior reversible encephalopathy syndrome, and we discuss the possible reasons for these findings and their relationship to the infection. ABBREVIATIONS: ACE2 ¼ angiotensin-converting enzyme 2; COVID-19 ¼ coronavirus 19; PRES ¼ posterior reversible encephalopathy syndrome; SARS-CoV-2 ¼ Severe Acute Respiratory Syndrome coronavirus 2 T he current pandemic of Severe Acute Respiratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
163
0
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(177 citation statements)
references
References 22 publications
3
163
0
11
Order By: Relevance
“…Infarct was reported in 13/124 (10%) and involved bilateral anterior [X : 9/242] and posterior [X : 4/242] circulation territories. Hemorrhages were noted in 7/124 (6%) and included: bilateral posterior parietooccipital area (J) (Franceschi et al, 2020) (Muhammad et al, 2020). Hematoma was also identified in one case report (1/124 (1%) and located in right subdural and frontal area [B] (Al-olama et al, 2020).…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…Infarct was reported in 13/124 (10%) and involved bilateral anterior [X : 9/242] and posterior [X : 4/242] circulation territories. Hemorrhages were noted in 7/124 (6%) and included: bilateral posterior parietooccipital area (J) (Franceschi et al, 2020) (Muhammad et al, 2020). Hematoma was also identified in one case report (1/124 (1%) and located in right subdural and frontal area [B] (Al-olama et al, 2020).…”
Section: Tablementioning
confidence: 99%
“…The midline structures of the brain were affected in 12/124 (10%) affected cases and mainly included abnormalities in the corpus callosum, i.e., hyperintensities [L (Hayashi et al, 2020); β (Zoghi et al, 2020)], hemorrhage [I] (Franceschi et al, 2020) Additionally, one of those patients [F] (Dixon et al, 2020) showed signs of swelling and hemorrhage in brain stem and hemorrhage in pons. Hyperintensities were noted in midbrain [A (Abdi et al, 2020); Z (Virhammar et al, 2020)] and pons [D (Asfar et al, 2020); β (Zoghi et al, 2020)].…”
Section: Topography Of Brain Abnormalities In Covid-19mentioning
confidence: 99%
“…Since the initial case reports describing COVID-19-associated acute hemorrhagic necrotizing encephalopathy [ 6 ], other neuroimaging findings in patients with COVID-19 have been reported, including encephalitis/meningitis [ [7] , [8] , [9] ], hemorrhagic posterior reversible encephalopathy syndrome (PRES) [ 10 , 11 ], acute disseminated encephalomyelitis (ADEM) [ 12 , 13 ], cerebral venous thrombosis [ [14] , [15] , [16] ], and acute ischemic stroke [ 8 , 16 , 17 ]. Over the past several months, the number of publications reporting COVID-19-related neuroimaging findings since the outbreak of SARS-CoV-2 has been unprecedented and evolving.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is possible that the cytokine storm that accompanies this disorder could be the cause of hemorrhagic strokes, as reported in a CO-VID-19 patient who developed an acute necrotizing encephalopathy associated with late parenchymal brain hemorrhages [4]. This massive release of cytokines may also damage and result in breakdown of the blood-brain barrier and cause hemorrhagic posterior reversible encephalopathy syndrome (PRES) [11]. Secondary hemorrhagic transformation of ischemic strokes has also been reported in COVID-19 patients [3,12].…”
mentioning
confidence: 99%